Prevalence of risk for chronic obstructive pulmonary disease amongst carpenters using lung function questionnaire - Subramanian, Visalakshi H.; Lokesh, Mukthapuram; Krishna Kumar , A. K. Vijay (International Journal Of Community Medicine And Public Health, 2023)
Background: An obstructive ventilatory pattern is a hallmark of chronic obstructive pulmonary disease (COPD), a slow-progressing respiratory condition that is frequently linked to cigarette use and can result in chronic respiratory failure. A case-finding tool called the lung function questionnaire (LFQ) is being created to help doctors choose which patients should undergo spirometry testing to confirm the presence of chronic obstructive pulmonary disease (COPD). Methods: Survey research study of 185 convenient sampling. Results: The results were obtained using lung function questionnaire. Statistical analysis shows that there is prevalence of risk for COPD amongst the carpenters. Conclusions: This study concludes that there is a risk of developing chronic obstructive pulmonary disease (COPD) in carpenters who are exposed to saw dust as more than half the samples have scored less than or equal to 18 which indicates the risk for COPD.